The Brilliance of the Text and the Depth of the Commentary: a New Edition of Descartesʼ Works in “La Bibliothèque de La Pléiadeˮ - Khoma, Oleg (Sententiae, 2025)
Review of Descartes, R. (2024). Œuvres (Vols. I-II). (J.-M. Beyssade, D. Kambouchner, Eds.). Paris: Gallimard.